Bacterial exposure risk to the endoscopist's face while performing endoscopy. Issue 1 (24th January 2023) - Hoshi, Kentaro; Kikuchi, Hidezumi; Narita, Koji; Fukutoku, Yukari; Asari, Taka; Miyazawa, Kuniaki; Murai, Yasuhisa; Sawada, Yohei; Tatsuta, Tetsuya; Hasui, Keisuke; Hiraga, Hiroto; Chinda, Daisuke; et al.
Abstract: Objectives: Gastrointestinal endoscopy increases the risk of bacterial exposure to endoscopists. However, before 2019, most endoscopists did not pay attention to microorganism transmission from patients. This study aimed to investigate the incidence of bacterial exposure to endoscopists' faces during gastrointestinal endoscopic procedures using the bacterial culture method. Methods: This was a single‐centered, retrospective study including endoscopists who performed various gastrointestinal endoscopy procedures at the Division of Endoscopy, Hirosaki University Hospital between August 31 and October 6, 2020. Endoscopists wore surgical masks and affixed pre‐sterilized films over them. Following the gastrointestinal endoscopic procedures, attached microbes were collected from the endoscopists' surface films using sterilized swabs. Collected microorganisms were cultured on tryptic soy agar and 5% sheep blood agar, and the incidence of bacterial exposure was determined by bacterial culture positivity. Cultured bacteria were identified by gram staining and 16S rRNA gene sequencing. Results: Bacterial culture positivity was 12.6%, and it was significantly higher in therapeutic than in diagnostic endoscopy. Notably, therapeutic endoscopy increased bacterial culture positivity in colonoscopy, but not in esophagogastroduodenoscopy. Staphylococci, including Staphylococcus epidermidis and Staphylococcus capitis, were the most commonly found bacteria in samples identified through 16S rRNA gene sequencing. Conclusions: The risk of bacterial exposure to the endoscopist's face was increased in colonoscopy treatment procedures. Therefore, endoscopists should be aware of the significant risk of microbial infection from scattering fluid that comes from the endoscopy's working channel.